THE CRISIS OF THE PARTHIAN STATE AND THE CONDITIONS OF THE COME TO POWER OF THE SASSONIAN STATE - Orzubek O‘ralov (TADQIQOTLAR.UZ, 2024)
Abstract. This article analyzes the conditions of the crisis of the Parthian state and the rise to power of the Sasanian state. The Parthian Empire's political instability, economic difficulties, and failures to combat external threats are considered factors that  led  to  its  downfall.  The  article  also  explores  the  process  of  the  rise  of  the Sassanids and the formation of new political structures that led them. In the historical context, the rise to power of the Sasanian state played an important role in unifying the  country  and  restoring  centralized  governance.  The  studied  processes,  the relationship between the Parthians and the Sasanians, also help to understand the impact of these historical changes on the region.